Alterations of bacterial clearance induced by endotoxin and tumor necrosis factor. - Koch, T (1993)
The purpose of the study was to investigate the potential influence of endotoxin and tumor necrosis factor (TNF) on immune function in terms of systemic clearance and organ distribution of injected Escherichia coli in a rabbit model. To enable quantification of the clearance process, defined numbers of exogenous E. coli (1.3 x 10(8) CFU) were injected intravenously 60 min after bolus application of TNF (4 x 10(5) U, n = 6), after infusion of endotoxin (40 micrograms/kg of body weight) for 1 h (n = 6) or 4 h (n = 6), or after saline infusion (controls, n = 6). Parameters monitored were arterial pressure, oxygen uptake, and rates of bacterial elimination from the blood. At 180 min after E. coli injection, the animals were sacrificed, and tissue samples of liver, kidney, spleen, and lung were collected for bacterial counts. Endotoxin infusion produced a significant delay in blood clearance compared with saline and TNF pretreatment. The diminished systemic bacterial elimination was associated with significantly higher numbers of E. coli in the organs, thus reflecting reticuloendothelial system dysfunction. TNF had no major influence on the elimination kinetics of bacteria but affected the tissue distribution pattern with increased accumulation of E. coli in the lung (up to 100-fold of control values; P < 0.001).